Co‐nanoencapsulated doxorubicin and Dz13 control osteosarcoma progression in a murine model. (2nd August 2012) - Tan, Mei Lin; Friedhuber, Anna M.; Dass, Crispin R.
Abstract Objectives Chitosan is a green (natural, abundant, biodegradable, biocompatible) biopolymer that can be formulated to encapsulate a variety of therapeutic compounds. This study aimed to investigate chitosan nanoparticles (NPs) as a means of improving delivery of the clinically used anti‐cancer agent doxorubicin (Dox) and the preclinical lead compound Dz13 oligonucleotide together. Methods A novel chitosan NP system encapsulating Dox and Dz13 was designed, biophysically characterised and tested in a clinically relevant model of the metastasising bone tumour, osteosarcoma (OS). Key findings By careful alteration of the concentration of the individual components, a final formulation of Dz13‐Dox NPs (DDNPs) was achieved, with high (>91%) loading of both compounds, which consisted of individual 50‐nm particles forming aggregates as large as 500 nm, with a large positive ζ‐potential. The DDNPs could be stored at various temperatures for a week without loss in activity but were prone to degradation in serum. DDNPs successfully inhibited OS tumour growth more effectively than treatment with NPs of Dz13 and Dox‐chitosan, as well as Dox administered intraperitoneally. Apart from inhibiting tumour growth, DDNPs protected the affected bone from substantial destruction by aggressive tumour growth and reduced the incidence of metastasis to the lungs without causing adverse effects in mice. Conclusion This NP is a promising formulation that could be useful for clinical management of OS.